Phylogenetic position of genera Acrostilicus Hubbard and Pachystilicus Casey (Staphylinidae, Paederinae) and their redescription - Żyła, Dagmara; Tokareva, Alexandra; Koszela, Katarzyna (European Journal of Taxonomy, 2022)
Acrostilicus Hubbard, 1896 and Pachystilicus Casey, 1905 are North American genera known from only one and two species, respectively, and have never been a subject of a modern revision. In fact, Acrostilicus was not even properly described as its author provided only a sketchy diagnosis of the genus and species. Here, we provide a redescription of the genus Acrostilicus and its species and illustrate the habitus and male genital features. For the first time, we also redescribe Pachystilicus and its two species, and provide their differential diagnoses. Additionally, we tested the phylogenetic position of both genera. They were scored into a morphological matrix supplemented with molecular data and the analyses were run using Bayesian inference and maximum likelihood methods. A total of 119 morphological characters and 4859 bp of nuclear (28S, TP, Wg, CADA, CADC, ArgK) and mitochondrial (COI) sequences were analysed for 46 taxa. The results confirmed that both Acrostilicus and Pachystilicus are members of the subtribe Stilicina, but at the same time challenged the monophyly of the subtribe in its current composition. Additionally, we provided further evidence for non-monophyly of the subtribe Medonina and discussed the biology of Acrostilicus and Pachystilicus.